Associations of Early Parental Concerns and Feeding Behaviors with Child’s Diet Quality through Mid-Childhood - Gingras, Véronique (Nutrients, 2020)
Parental feeding practices have been associated with children’s dietary intakes, yet the directionality of these associations remains unclear. Among 1172 mother-child pairs from Project Viva, we aimed to examine associations of parental concerns and feeding behaviors at 2 years (behaviors dichotomized as yes vs. no), with diet quality (Youth Healthy Eating Index; YHEI) in early (mean 3.2, SD 0.3 years; n = 1076) and mid-childhood (mean 7.8, SD 0.7 years; n = 993). We used multivariable linear regression models adjusted for sociodemographic characteristics, parental body mass index (BMI), maternal diet quality in pregnancy, and child’s BMI z-score and diet quality at 2 years. Early parental concerns about their child becoming overweight (15%) was associated with lower YHEI (β −1.54 points; 95%CI −2.75, −0.33; fully adjusted model) in early childhood. Early parental concerns about their child becoming underweight (7%) was associated with lower YHEI (−2.19 points; −4.31, −0.07) in early childhood, but the association was attenuated after adjustment for child’s BMI z-score and diet quality at 2 years. We did not find associations of parental restrictive feeding (8%) and parental pressure to eat (47%) with child’s YHEI through mid-childhood. In conclusion, we found no evidence that early parental concerns and feeding behaviors independently contribute to child’s diet quality through childhood.